IL-4 type 1 receptor signaling up-regulates KCNN4 expression, and increases the KCa3.1 current and its contribution to migration of alternative-activated microglia - Ferreira, Roger; Lively, Starlee; Schlichter, Lyanne C. (Frontiers in Cellular Neuroscience, 2014)
The Ca2+-activated K+ channel, KCa3.1 (KCNN4/IK1/SK4), contributes to ‘classical’, pro-inflammatory activation of microglia, and KCa3.1 blockers have improved the outcome in several rodent models of CNS damage. For instance, blocking KCa3.1 with TRAM-34 rescued retinal ganglion neurons after optic nerve damage in vivo and, reduced p38 MAP kinase activation, production of reactive oxygen and nitrogen species, and neurotoxicity by microglia in vitro. In pursuing the therapeutic potential of KCa3.1 blockers, it is crucial to assess KCa3.1 contributions to other microglial functions and activation states, especially the IL-4-induced ‘alternative’ activation state that can counteract pro-inflammatory states. We recently found that IL-4 increases microglia migration—a crucial function in the healthy and damaged CNS—and that KCa3.1 contributes to P2Y2 receptor-stimulated migration. Here, we discovered that KCa3.1 is greatly increased in alternative-activated rat microglia and then contributes to an enhanced migratory capacity. IL-4 up-regulated KCNN4 mRNA (by 6 hr) and greatly increased the KCa3.1 current by 1 day, and this required de novo protein synthesis. The increase in current was sustained for at least 6 days. IL-4 increased microglial migration and this was reversed by blocking KCa3.1 with TRAM-34. A panel of inhibitors of signal-transduction mediators was used to analyze contributions of IL-4-related signaling pathways. Induction of KCNN4 mRNA and KCa3.1 current was mediated specifically through IL-4 binding to the type I receptor and, surprisingly, it required JAK3, Ras/MEK/ERK signaling and the transcription factor, AP-1, rather than JAK2, STAT6 or PI3K. The same receptor subtype and pathway were required for the enhanced KCa3.1-dependent migration. In providing the first direct signaling link between an IL-4 receptor, expression and roles of an ion channel, this study also highlights the potential importance of KCa3.1 in alternative-activated microglia.